Aplectana nordestina n. sp. (Nematoda: Cosmocercidae) parasitizing Leposternon polystegum (Squamata: Amphisbaenidae) from Northeastern, Brazil - Amorim, Darciane Maria De; Silva, Lidiane Aparecida Firmino Da; Morais, Drausio Honorio; Silva, Reinaldo José Da; Ávila, Robson Waldemar (Zootaxa, 2017)
There are currently 760 reptile species known in Brazil, from which about 70 are amphisbaenians with 25 species recorded in the Brazilian northeast (Vanzolini 2002; Gomes & Maciel 2012; Costa & Bérnils, 2014; Roberto et al., 2014). Leposternon polystegum Duméril, is a widespread species distributed in the Amazon, Atlantic Forest, Cerrado, and Caatinga biomes (Porto et al., 2000; Ribeiro et al., 2011). The diet is composed mainly by ants, termites, and coleopteran larvae (Barros-Filho & Valverde, 1996; Gomes et al., 2009).